A gesture life - Lee, Change - rae; Quinn, Marysarah (New York Riverhead books, 1999)
A Geture life is the touching, multilayered rumination of an uneasy psyche. It also a tragic, horrifying page - turner, whose evocation of wartime victims is unforgettable ... A deeply involving tale, no less so because we realize, that we can't trust Hata's version of events
A New York Times Notable Book
American corner
A finalist for the New Yorker book Award
An ALA notable book of the year
Talk magazine's best book of 1999
Winner of the Anisfield - Wolf Literary Award
Keywords: English fiction; Japanese American -- fiction; Japanese American -- New York; The second world war -- 1939 - 1945